Single-molecule folding mechanisms of the apo- and Mg(2+)-bound states of human neuronal calcium sensor-1 - Naqvi MM; Heidarsson PO; Rodriguez Otazo M; Mossa A; Kragelund BB; Cecconi C (Biophysical Society)
Neuronal calcium sensor-1 (NCS-1) is the primordial member of a family of proteins responsible primarily for sensing changes in neuronal Ca(2+) concentration. NCS-1 is a multispecific protein interacting with a number of binding partners in both calcium-dependent and independent manners, and acting in a variety of cellular processes in which it has been linked to a number of disorders such as schizophrenia and autism. Despite extensive studies on the Ca(2+)-activated state of NCS proteins, little is known about the conformational dynamics of the Mg(2+)-bound and apo states, both of which are populated, at least transiently, at resting Ca(2+) conditions. Here, we used optical tweezers to study the folding behavior of individual NCS-1 molecules in the presence of Mg(2+) and in the absence of divalent ions. Under tension, the Mg(2+)-bound state of NCS-1 unfolds and refolds in a three-state process by populating one intermediate state consisting of a folded C-domain and an unfolded N-domain. The interconversion at equilibrium between the different molecular states populated by NCS-1 was monitored in real time through constant-force measurements and the energy landscapes underlying the observed transitions were reconstructed through hidden Markov model analysis. Unlike what has been observed with the Ca(2+)-bound state, the presence of Mg(2+) allows both the N- and C-domain to fold through all-or-none transitions with similar refolding rates. In the absence of divalent ions, NCS-1 unfolds and refolds reversibly in a two-state reaction involving only the C-domain, whereas the N-domain has no detectable transitions. Overall, the results allowed us to trace the progression of NCS-1 folding along its energy landscapes and provided a solid platform for understanding the conformational dynamics of similar EF-hand proteins.
Keywords: Cations, Divalent; Computer Simulation; Escherichia coli; Humans; Kinetics; Magnesium; Markov Chains; Neuronal Calcium-Sensor Proteins; Neuropeptides; Optical Tweezers; Protein Folding; Spectrum Analysis; Thermodynamics; 02 Physical Sciences; 03 Chemical Sciences; 06 Biological Sciences